Automatic collision avoidance system with many targets, including maneuvering ones - С. Зинченко; П. Носов; В. Матейчук; П. Маменко; И. Попович; О. Грошева (Қарағанды университетінің хабаршысы. Физика сериясы)
The article considers the issues of automatic collision avoidance with many targets, including maneuvering ones, which is especially important when navigating a vessel in narrownesses. Was made a brief review of literature devoted to the problem of collision avoidance and conclusion was drown on the relevance of developing such systems. There were developed mathematical and algorithmic support of the combined collision avoidance with many targets, including maneuvering ones. Based on the synthesized algorithms, there was developed software in the MATLAB environment for a simulator of an onboard controller of a ship control system, the operability and efficiency of mathematical, algorithmic and software was tested in a closed circuit with a Navi Trainer 5000 navigation simulator for various types of ships, navigation areas and weather conditions. The experiments confirmed the efficiency of the proposed method and algorithms and allow to recommend them for practical use in the development of modules for automatic collision avoidance with many targets, including maneuvering ones, an onboard controller of the ship’s control system.